TINDAK PIDANA PENCEMARAN NAMA BAIK BERDASARKAN PASAL 310 KUHP - Faris Septyan R (Gapenas Publisher, 2022)
The purpose of this research is to find out what actions are included in the criminal act of defamation and what elements are contained in Article 310 of the Criminal Code and Article 27 paragraph (3) of the ITE Law relating to defamation. By using the normative juridical research method, it is concluded: 1. That in the criminal act of defamation there are acts which include insults contained in Article 310 of the Criminal Code, Article 311 of the Criminal Code, Article 315 of the Criminal Code, Article 317 of the Criminal Code, and Article 318 of the Criminal Code. 2. The criminal act of Defamation has elements included in it. These elements are the basis for us to assess the existence of an act of defamation, in these elements we can categorize every act committed by the perpetrator. If the perpetrator commits defamation by slandering someone, what we see are the elements included in the slander, whether it can be categorized in slander or more clearly the perpetrator committed a criminal act in Article 311 of the Criminal Code. We have to look at the elements in it, if indeed the perpetrator did what is in the elements of Article 311 of the Criminal Code, the perpetrator could be imprisoned under that article